Al-Zinki, Najm al-Din Qadir. “ʿAbd al-Razzāq al-Sanhūrī and His Codification Project: A Study and Assessment,” Year 7, Issue 27 (Winter 1422 AH/ 2001 CE), Pp. 63-94. - الزنكي نجم الدين قادر (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2001)
Najm al-Din al-Zinki’s article introduces ʿAbd al-Razzāq al-Sanhūrī and the terms of his codification project, reviewing the history of codification in Islamic countries before al-Sanhūrī’s project, and explaining al-Sanhūrī’s position towards codification, ancient Egyptian Law, and towards laws throughout the world. It discusses the premises that led al-Sanhūrī to formulate his new law, his sources of the law, and his evaluation of the project. It then addresses the transfer of codification to Arab countries, explaining al-Sanhūrī’s strategy in applying the principles of Shariʿah. It provides an analysis and assessment of the views of some writers who refer to the project as one of the unparalleled laws from a technical perspective, though al-Sanhūrī holds that it cannot be described as Islamic law, despite the clarity of his call for the application of Shariʿah law, as reflected in his writings and his personal papers.